"Biocompatible" Neutral pH Low‐GDP Peritoneal Dialysis Solutions: Much Ado About Nothing?. Issue 2 (March 2017) - Misra, Paraish S.; Nessim, Sharon J.; Perl, Jeffrey
Abstract: Adverse outcomes in peritoneal dialysis (PD), including PD related infections, the loss of residual kidney function (RKF), and longitudinal, deleterious changes in peritoneal membrane function continue to limit the long‐term success of PD therapy. The observation that these deleterious changes occur upon exposure to conventional glucose‐based PD solutions fuels the search for a more biocompatible PD solution. The development of a novel PD solution with a neutral pH, and lower in glucose degradation products (GDPs) compared to its conventional predecessors has been labeled a "biocompatible" solution. While considerable evidence in support of these novel solutions' biocompatibility has emerged from cell culture and animal studies, the clinical benefits as compared to conventional PD solutions are less clear. Neutral pH low GDP (NpHLGDP) PD solutions appear to be effective in reducing infusion pain, but their effects on other clinical endpoints including peritoneal membrane function, preservation of RKF, PD‐related infections, and technique and patient survival are less clear. The literature is limited by studies characterized by relatively few patients, short follow‐up time, heterogeneity with regards to the novel PD solution type under study, and the different patient populations under study. Nonetheless, the search for a more biocompatible PD solution continues with emerging data on promising non glucose‐based solutions.